Feedback Challenges in the Formative Assessment of the Interinstitutional Program of Teaching-Service-Community Interaction: the Students’ Perspective - Miranda,Guilherme Roberto Naves (2020)
Abstract: Introduction: This present study assesses the use of the feedback mechanism in the formative assessment during medical training, considering this instrument is of great importance for this training stimulation, which is based on active teaching methodologies. The study aims to characterize the application of this tool and to identify possible failures in its application in the daily routine of the PINESC module in the Anhanguera University (Uniderp) medical course. Method: This is a quantitative, sectional research, including students from the first to the eighth semesters of the medical course, attending the PINESC longitudinal module. In the data collection, a questionnaire was used with questions related to the formative assessment performed by the preceptors, which is reported to the students according to the sample calculation. The feedback is the core activity of the formative assessment and allows the development of reflective and self-evaluation capacities and the development of skills. However, the use of feedback still faces barriers, mainly due to the difficulty of the evaluators in listing negative points and capabilities of the evaluated individuals. Result: In this study, some shortcomings and positive points were reported regarding the application process of this tool, listing and suggesting improvements for a better use of feedback and thus a more favorable academic achievement. Conclusion: In conclusion, as the basis of formative evaluation, the feedback still shows many weaknesses regarding its form and application.